Electrical properties of neutron-irradiated silicon and GaAs commercial diodes - Che Omar, Nuurul Iffah; Hasbullah, Nurul Fadzlin; Alang Md Rashid, Nahrul Khair; Abdullah , Jaafar (2012)
Neutron radiation testing was performed on silicon and GaAs diodes to investigate changes in the device parameters after neutron exposure. Californium-252 source was used to irradiate these diodes up to total dose of 1117.87mSv. The effects of nuclear radiation on the forward and reverse current-voltage (I-V) characteristics of Silicon and GaAs diodes were studied at room temperature. It was found that the magnitudes of forward bias electrical characteristics were in most instances unaffected by irradiation in both materials. The increments in TSKS5400S GaAs infrared emitting diode reverse currents were large after irradiation. These changes were interpreted as effects of displacement damage generating generation-recombination currents due to defects created. However, reverse bias (RB) characteristics of 1N4148 silicon diodes showed decrement in dark current. This is attributed to the type of diodes used.